2018
DOI: 10.1007/s10072-018-3450-y
|View full text |Cite
|
Sign up to set email alerts
|

The 100 most-cited articles in Parkinson’s disease

Abstract: The present study provides historical perspectives on the progress of PD research and highlights trends and academic achievements in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Several recent studies have identified and analysed highly cited articles in fields such as gastroenterology, thoracic surgery, orthopaedics, neurosurgery, neurology and ophthalmology . To the best of our knowledge, however, no such studies in the field of LC have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have identified and analysed highly cited articles in fields such as gastroenterology, thoracic surgery, orthopaedics, neurosurgery, neurology and ophthalmology . To the best of our knowledge, however, no such studies in the field of LC have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, a bibliometric analysis related to Alzheimer's disease (AD) has been reported by Sorensen. In 2018, Xue et al reported “The 100 most-cited articles in Parkinson's disease” (PD) (Xue et al, 2018 ) for the first time. However, no top-cited bibliometric analysis has been conducted on the whole field of the neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…It makes it more accessible for researchers and others outside the field to have an overview of its directions and needs 7 . The literature does present bibliometric analysis on various themes, such as neurocritical care 6 , back pain 8 , essential tremor 7 , Parkinson's disease 9 , and deep brain stimulation 10 .…”
Section: Introductionmentioning
confidence: 99%